Cloud computing: Concepts and technologies - Manvi, Sunil Kumar; Shyam, Gopal Krishna (Abingdon, Oxon CRC Press, 2021)
Comprehensive and timely, Cloud Computing: Concepts and Technologies offers a thorough and detailed description of cloud computing concepts, architectures, and technologies, along with guidance on the best ways to understand and implement them. It covers the multi-core architectures, distributed and parallel computing models, virtualization, cloud developments, workload and Service-Level-Agreements (SLA) in cloud, workload management.